Manilkara zapota (L.) P. royen leaf mitigates colitis-associated colon cancer through anti-inflammatory modulation in BALB/C Mice - Mohd Esa, Norhaizan; Hamzah, Hazilawati; Shafie, Nurul Husna; Mohd Tamsir, Norain (Hindawi Limited, 2024)
Colitis-associated colon cancer (CAC) arises from prolonged inflammation of the inner colon lining. An alternative approach to treating or preventing CAC involves the use of natural products such as Manilkara zapota (L.) P. Royen or M. zapota, which has been studied for its medicinal and pharmacological properties. Previous research has demonstrated the anticancer effects of M. zapota leaf aqueous extract (MZLAE) on colon cancer cells. However, no animal study has investigated the effects of MZLAE on CAC. Therefore, this study aimed to assess the potential anti-inflammatory effects of MZLAE on CAC in mice. In the present study, CAC was induced using azoxymethane (AOM) and dextran sodium sulphate (DSS). The mice were randomly assigned into five groups: (a) normal, (b) AOM/DSS, (c) AOM/DSS + 50 mg/kg MZLAE, (d) AOM/DSS + 100 mg/kg MZLAE, and (e) AOM/DSS + 200 mg/kg MZLAE. Various parameters including disease activity index (DAI), colon length and weight, reactive oxygen species (ROS), superoxide, superoxide dismutase (SOD), histopathological assessment, and proinflammatory cytokines expression were analysed. The results indicated that MZLAE improved DAI scores, colon length, colon histological dysplasia and inflammation scores, and SOD level, while also reducing ROS production and expression of proinflammatory cytokines (tumour necrosis factor-alpha (TNF- α) and interleukin 6 (IL-6)). In conclusion, this study suggests that MZLAE may serve as a promising source of antioxidants and anti-inflammatory agents for alleviating CAC.